2019
DOI: 10.1093/sleep/zsz205
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the cardiometabolic benefits of sleep in older women: exploring the 24-hour day

Abstract: Study Objectives Activities throughout the day, including sleep, sedentary behavior (SB), light-intensity physical activity (LIPA), and moderate to vigorous physical activity (MVPA) are independently associated with cardiometabolic health. Few studies have examined interrelationships between sleep and 24-hour activity and associations with cardiometabolic risk. The objective of this study is to understand how replacing time in SB, LIPA, or MVPA with sleep impacts cardiometabolic risk. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 58 publications
2
9
0
Order By: Relevance
“…As far as we know, there are no previous publications using isotemporal substitution in patients with RA, but during the last decade, the method has been used in other studies to increase knowledge on the relationships between the 24‐hour activity behaviors and CV health (7). In concordance with our results, a recently published study of older women presented a favorable effect on waist circumference and BMI with a reallocation of time from SB to sleep for the subgroup with shorter sleep duration (<8 hours) (47). In a study conducted in 200 000 participants followed up on for 4.2 years, Stamatakis et al revealed lower all‐cause mortality when replacing sitting time with sleep or with physical activity in participants sleeping 7 or fewer hours per day (48).…”
Section: Discussionsupporting
confidence: 92%
“…As far as we know, there are no previous publications using isotemporal substitution in patients with RA, but during the last decade, the method has been used in other studies to increase knowledge on the relationships between the 24‐hour activity behaviors and CV health (7). In concordance with our results, a recently published study of older women presented a favorable effect on waist circumference and BMI with a reallocation of time from SB to sleep for the subgroup with shorter sleep duration (<8 hours) (47). In a study conducted in 200 000 participants followed up on for 4.2 years, Stamatakis et al revealed lower all‐cause mortality when replacing sitting time with sleep or with physical activity in participants sleeping 7 or fewer hours per day (48).…”
Section: Discussionsupporting
confidence: 92%
“…Physical activity levels measured as total steps per day and total sleep time in hours were derived based on accelerometry data, as previously described. 16,26,27 Physical function was assessed by the Established Populations for Epidemiological Studies in the Elderly short physical performance battery (SPPB). 28 Finally, we derived a variable indicating the number of comorbidities (cancer, cerebrovascular disease, cardiovascular disease, diabetes, frequent falls, depression, osteoarthritis, and chronic obstructive pulmonary disease) among OPACH participants.…”
Section: Covariatesmentioning
confidence: 99%
“…With increased age, about one-third of the elderly have a night sleep duration that is either too long or too short. 5 Extreme night sleep duration may impair vascular endothelial function by accelerated lipid deposition 6 and may also cause deterioration of the vasculature by adversely affecting muscle strength. 7 Although previous studies have suggested that extreme night sleep duration is related to CVD risk, especially in the elderly, the relationship may be J-shaped, 8 9 U-shaped 10 or neither.…”
Section: Open Accessmentioning
confidence: 99%
“…Higher triglycerides and cholesterol related to lipid deposition appear in long sleepers. 6 Lipid deposition in the large and middle arteries promotes the formation of atherosclerotic plaques, thickening and hardening of arterial walls, narrowing of the lumen, and ultimately leading to ischaemic diseases. In the Fasa Cohort Study, short night sleep duration was associated with a higher predicted risk of CVD, 27 possibly attributable to lower cholesterol and triglyceride levels compared with the subjects in this study.…”
Section: Night Sleep Duration and Cvd Riskmentioning
confidence: 99%